Application of CAD/CAM in the design of machining process and tooling devices for flange tube - Musa Alhaji Ibrahim,; Huang, Kai; Mustapha Mukhtar Usman, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Recently, computer-aided design and computer aided manufacturing (CAD/CAM) is largely applied in universal machinery due to the accelerated development of computer technologies. Owing to the technical application of CAD/CAM tool in the manufacturing industry, enterprises have progressively changed their traditional approaches to design and manufacture of products. The CAD module provides product designers with capabilities of designing product model by feature-based design and obtaining product data. The product model is displayed on a screen in the CAD environment before transferring it downstream to the CAM module. This paper presents the application of CAD/CAM in solid modelling, design of machining process, fixture design and virtual manufacture of a flanged tube. Pro/Engineer (Pro/E) Wildfire 4.0 was used to create the three dimensional (3D) model of the flange tube based on its two-dimensional drawing (2D) blank drawing and the mould was designed and created using the same software. The mould creation was based on the clamping and positioning devices of the flange tube being manufactured. The technical schedule of the flange tube was worked out including the choice of machining method, machine tool, cutting tool and selection and computation of machining parameters based on finished drawing the flange tube. Two dedicated fixtures for holding the flange tube in the machine tool were designed and finally Master CAM 9.0 software was applied to the virtual machining of the mould. It is concluded that CAD/CAM tool is important in manufacturing technology as it automates the manufacturing process thereby saving time, energy, cost, and making production highly flexible.